High‐Quality Epitaxial Five‐Layer Aurivillius Films with In‐Plane Ferroelectricity for Electrocaloric Cooling - Sara Lafuerza; Javier Blasco; Marco Evangelisti; Gloria Subías; David Gracia; José Á. Pardo; Eduardo Barriuso; Xavier Torrelles; Jessica Padilla‐Pantoja; José M. Caicedo; José Santiso (Advanced Electronic Materials, 2025)
Abstract High‐quality purely c‐axis oriented epitaxial thin films of the Aurivillius phase Sr2Bi4Ti5O18 with n = 5 (Sr,Bi)TiO3 perovskite‐like layers, are grown on SrTiO3 substrates by pulsed laser deposition. The highest crystalline quality is obtained with a 20 wt.% Bi‐excess target and average stacking order values in the proximity of the ideal value n = 5 are attained for an optimum deposition temperature of 650 °C. Scanning transmission electron microscopy reveals regions with n ranging from 4 to 6 around an average thickness of n = 5, in agreement with the X‐ray diffraction analysis. Interdigital electrodes are used to probe the in‐plane polarization and survey the electrocaloric properties. A maximum adiabatic temperature change of ΔT ∼ 0.95 °C for an electric field of 150 kV cm−1 is observed at ≈135 °C. Larger values are expected at higher temperatures around the ferroelectric Curie temperature, TC. Since TC of Sr2Bi4Ti5O18 can be tuned by codoping, the findings pave the way toward a large electrocaloric effect at ambient temperature.